2007
DOI: 10.1103/physrevlett.98.205301
|View full text |Cite
|
Sign up to set email alerts
|

Bose-Einstein Condensation in SolidHe4

Abstract: We present neutron scattering measurements of the atomic momentum distribution, n(k), in solid helium under a pressure p = 41 bars and at temperatures between 80 mK and 500 mK. The aim is to determine whether there is Bose-Einstein condensation (BEC) below the critical temperature, Tc = 200 mK where a superfluid density has been observed. Assuming BEC appears as a macroscopic occupation of the k = 0 state below Tc, we find a condensate fraction of n0 = (-0.10 ±1.20)% at T = 80 mK and n0 = (0.08±0.78)% at T =12… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…A condensate fraction has not been observed in crystalline solid helium 40,68,69 at these pressures, even when the surface area is large. 69 An upper limit of n 0 ≤ 0.3 % has been set.…”
Section: -67mentioning
confidence: 85%
See 1 more Smart Citation
“…A condensate fraction has not been observed in crystalline solid helium 40,68,69 at these pressures, even when the surface area is large. 69 An upper limit of n 0 ≤ 0.3 % has been set.…”
Section: -67mentioning
confidence: 85%
“…The lowest two are a 3 = ∇ 2 v(r) /6 and a 4 = (∇v) 2 /3 where v(r) is the total potential seen by the struck atom. In applications 34,40 we have found that β 4 is negligible. Similarly the a 54 term in β 5 and the a 62 term in β 6 are also small and can be neglected.…”
Section: B Observed Dynamic Structure Factormentioning
confidence: 89%
“…Observation of BEC in solid helium would be an unambiguous verification of superflow but, as yet, has not been observed [17][18][19] . To better understand BEC in dense systems we have measured 20 the condensate fraction in liquid 4 He at low temperature as a function of pressure up to solidification, p = 25.3 bar.…”
mentioning
confidence: 90%
“…This includes the MARI [24][25][26][27][28][29] , PHOENIX [30][31][32][33][34] , and eVS 35 spectrometers. There is both convergence and divergence in the results of these studies.…”
Section: Introductionmentioning
confidence: 99%